Anisotropic Strain‐Mediated Symmetry Engineering and Enhancement of Ferroelectricity in Hf0.5Zr0.5O2/La0.67Sr0.33MnO3 Heterostructures. (28th November 2022) - Liu, Kai; Jin, Feng; Zhang, Xingchang; Liu, Kuan; Zhang, Zixun; Hua, Enda; Zhang, Jinfeng; Ye, Huan; Gao, Guanyin; Ma, Chao; Wang, Lingfei; Wu, Wenbin
Abstract: Hafnium‐based binary oxides have attracted considerable attention due to their robust ferroelectricity at the nanoscale and compatibility with silicon‐based electronic technologies. To further promote the potential of Hafnium oxides for practical device applications, it is essential to effectively harness the interplay between structural symmetry, domain configuration, and ferroelectricity. Here, using Hf0.5 Zr0.5 O2 /La0.67 Sr0.33 MnO3 (HZO/LSMO) heterostructures as a model system, the anisotropic strain‐mediated symmetry engineering and ferroelectricity enhancement are systematically investigated. By growing the heterostructures on (110)‐oriented perovskite substrates, considerable anisotropic strain is imposed on the LSMO bottom electrodes. Such an anisotropically‐strained LSMO layer acts as a structural template and effectively tune the structural symmetry, polar/non‐polar phase ratio, and ferroelectricity of the HZO top layer. Specifically, the anisotropic tensile strain stabilizes the ferroelectric rhombohedral and orthorhombic phases, thus enhancing the remnant polarization ( P r ) up to 22 µC cm −2 . In contrast, the anisotropic compressive strain facilitates the formation of non‐ferroelectric tetragonal phases, leading to a suppressed P r down to 8 µC cm −2 . These findings provide a guideline for understanding and modulating the intrinsic structure‐ferroelectricity relationship of HZO through anisotropic strain‐mediated symmetry engineering, which may shed light on the development of hafnium‐oxide‐based electronic devices. Abstract : The evolutions of ferroelectricity, structural symmetry, and domain configuration are explored in anisotropic strained Hf0.5 Zr0.5 O2 /La0.67 Sr0.33 MnO3 (HZO/LSMO) heterostructures. It is found that the anisotropic strain imposed on the LSMO bottom electrode effectively tunes the polar/nonpolar phase ratio of the HZO thin films and thus achieves considerable enhancement in ferroelectricity.